2017
DOI: 10.1016/j.ebcr.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation for generalized epilepsy with febrile seizures plus (GEFS+) accompanying seizures with impaired consciousness

Abstract: Generalized epilepsy with febrile seizures plus (GEFS+) is characterized by childhood-onset epilepsy syndrome. It involves febrile seizures and a variety of afebrile epileptic seizure types within the same pedigree with autosomal-dominant inheritance. Approximately 10% of individuals with GEFS+ harbor SCN1A, a gene mutation in one of the voltage-gated sodium channel subunits. Considerably less common are focal epilepsies including focal seizures with impaired consciousness. We report vagus nerve stimulation (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…identified 45 articles in their primary searches using the key-words mentioned in the methods section. Identification of relevant articles in English revealed one selection discrepancy between the two authors: one recently published case report by Hanaya et al describing efficacy of VNS in a patient with a confirmed SCN1A mutation and genetic epilepsy with febrile seizures plus (GEFS+) [21]. GEFS+ refers to a familial epilepsy syndrome comprising a spectrum of phenotypes from febrile seizures to DS in which SCN1A mutations can be found in 10% of patients [34].…”
Section: Study Selectionmentioning
confidence: 99%
“…identified 45 articles in their primary searches using the key-words mentioned in the methods section. Identification of relevant articles in English revealed one selection discrepancy between the two authors: one recently published case report by Hanaya et al describing efficacy of VNS in a patient with a confirmed SCN1A mutation and genetic epilepsy with febrile seizures plus (GEFS+) [21]. GEFS+ refers to a familial epilepsy syndrome comprising a spectrum of phenotypes from febrile seizures to DS in which SCN1A mutations can be found in 10% of patients [34].…”
Section: Study Selectionmentioning
confidence: 99%
“… 2 - 6 The phenotype represented in our reported case, showing both isolated and frequent seizure events. The VNS implantation has been reported as an effective termination method for epilepsy-related channelopathies; 7 - 8 however, the current case was the first to utilize VNS in the treatment of KCNMA1 mutation–related epilepsy, specifically. Furthermore, VNS can be used as a suppressor method for refractory status epilepticus related to this gene mutation.…”
Section: Discussionmentioning
confidence: 92%
“…Similar results have since been reported in genetic epilepsy with febrile seizures plus (GEFS+) and Dravet syndrome patients. In both of these, VNS seemed to exert a beneficial role in both seizure reduction and cognitive functions (12,13).…”
Section: Discussionmentioning
confidence: 99%